Frequency of EGFR mutations in 907 lung adenocarcioma patients of Indian ethnicity. - Anuradha Chougule; Kumar Prabhash; Vanita Noronha; Amit Joshi; Abhishek Thavamani; Pratik Chandrani; Pawan Upadhyay; Sagarika Utture; Saral Desai; Nirmala Jambhekar; Amit Dutt (PLoS ONE, 2013)
BACKGROUND:During the past decade, the incidence of EGFR mutation has been shown to vary across different ethnicities. It occurs at the rate of 10-15% in North Americans and Europeans, 19% in African-Americans, 20-30% in various East Asian series including Chinese, Koreans, and Japanese. Frequency of EGFR mutations in India however remains sparsely explored. METHODOLOGY/PRINCIPAL FINDINGS:We report 23% incidence of Epidermal growth factor receptor (EGFR) mutations in 907 Non small cell lung cancer (NSCLC) patients of Indian ethnicity, in contrast to 10-15% known in Caucasians and 27-62% among East Asians. In this study, EGFR mutations were found to be more common in never-smokers 29.4% as compared to smokers 15.3%. Consistent with other populations, mutation rates among adenocarcinoma-males were predominantly lower than females with 32% incidence. However unlike Caucasians, EGFR mutation rate among adenocarcinoma-never-smoker females were comparable to males suggesting lack of gender bias among never smokers likely to benefit from EGFR targeted therapy. CONCLUSIONS/SIGNIFICANCE:This study has an overall implication for establishing relevance for routine EGFR mutation diagnostics for NSCLC patients in clinics and emphasizes effectiveness for adoption of EGFR inhibitors as the first line treatment among Indian population. The intermediate frequency of EGFR mutation among Indian population compared to Caucasians and East Asians is reminiscent of an ancestral admixture of genetic influence from Middle Easterners, Central Asians, and Europeans on modern- Indian population that may confer differential susceptibility to somatic mutations in EGFR.